Doing Hijrah Through Music: A Religious Phenomenon Among Indonesian Musician Community - Qomaruzzaman, Bambang; Busro, Busro (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This paper studies the variants of hijrah movements among Muslim youths in Bandung, Indonesia, in responding music. Hijrah (to migrate spiritually) was first interpreted as abandoning the past sinful life into the path of Islam. In its development, it is defined as leaving behind “un-Islamic” activities, including music. The latter meaning of hijrah conveys to ex-musicians performing hijrah to completely abandon music and even destroys their musical instruments. Among hijrah groups, Gerakan Pemuda Hijrah conveys the detrimental effects of music for Islamic morality and faith. For them, music will drive Muslims to the jāhilīyah (ignorance), shirk (polytheism) and bid‘ah (innovation/heresy). Amidst this situation, Komunitas Musisi Mengaji (KOMUJI) emerges to practicing hijrah by performing musical activities and even employing “musicking” as a way to attain the true path of Islam. This paper reveals the different views of those groups concerning music and hijrah, as well as shows an alternative path amid Islamism and globalization.